Gelatin particle indirect agglutination and enzyme-linked immunosorbent assay for diagnosis of strongyloidiasis using Strongyloides venezuelensis antigen - Huaman M.C. (2003)
We appreciate the valuable comments of Dr Franklin Neva to improve the manuscript. We thank Tetsuo Yanagi for technical support and the staff of the Laboratory of Parasitology, Institute of Tropical Medicine, Universidad Peruana Cayetano Heredia for helping us with sample collection. This work was partially supported by the Japanese International Cooperation Agency (JICA) and the Consejo Nacional de Ciencia y Tecnologia (CONCYTEC), Peru.